Super Refractory Status Epilepticus in Neuropsychiatric Systemic Lupus Erythematosus: A Rare Case - Mehmet Fatih GÖL; Mehmet Fatih YETKİN; Elif Gülşen KÖSE; Füsun Ferda ERDOĞAN (Archives of Epilepsy, 2019)

(untitled)
Systemic lupus erythematosus (SLE) is an autoimmune disease with extensive organ involvement. Neuropsychiatric-SLE (NP-SLE) includes the involvement of the central nervous system, and has an epileptic seizure rate of 6.7% to 14.4%. The prognosis of epilepsy in NP-SLE patients is fairly good, usually long-term antiepileptic treatment is not needed and only 24% of patients require polytherapy. Less than half of seizures are focal onset seizures and focal onset seizure secondary status epilepticus is rarely seen in NP-SLE. Presently described is the case of a 17-year-old woman with focal onset seizures and impaired awareness with right lower extremity weakness who had been diagnosed with SLE and whose seizures were not controlled despite antiepileptic treatment. This report was presented to draw attention to the management of super refractory status epilepticus and to review neuropsychiatric-SLE.